The influence of Islamic Banking on Financial Inclusion and Economic Development in Uganda. - Idris Kawooya (Uganda Christian University, 2024)
This research examines the impact of Islamic banking on financial inclusion and economic development in Uganda. In Uganda's secular banking sector, the idea of Islamic banking is a recent development. Islamic banking is governed by the Financial Institutions (Amendment) Act of 2016, which also gives it existence. The study clarifies how Islamic banks will affect Uganda's economy and financial inclusion generally, even though they must operate in line with Shari'ah principles. It also highlights how these principles may be restricted by Central Bank policies and regulations, particularly the Financial Institutions (Islamic Banking) Regulations 2018 and other policies. The authorities want to conduct thorough research and work hard to create a framework of laws and regulations that would effectively support Uganda's Islamic finance sector.Efforts ought to be undertaken to adjust the current framework in order to deliver superior goods and services while adhering to Islamic law.All parties involved should be aware of the current state of affairs and strive to create an economic system that is genuinely reflective of the precepts of Islam.In conducting the study, the researcher relied on qualitative methodology. Accordingly, data was collected using both primary and secondary source of information, using the doctrinal research. The researcher used qualitative methods to carry out the investigation The key findings show that the adoption of Islamic banking is likely to have some legislative challenges which cannot effectively serve the true operation of Islamic banking. It has also been discovered that the modes of Islamic Banking practiced in Uganda have led and will lead to Economic development and financial inclusion through the regulation and implementation of Islamic laws particularly the financial institutions act 2016. The study recommends that to ensure a proper and supporting Islamic banking legal system in Uganda, amendments in existing laws, which are likely to be repugnant to Islamic banking, are required to promote Islamic banking law compliant products and adopting other legal methods like alternative dispute resolution among others.